The need for professional development in improving teaching practices in primary schools in Kosovo - Kurteshi, Voglushe; Bunjaku-Isufi, Mirlinda; Rrustemi, Jehona (Frontiers in Education, 2025)
IntroductionThis study investigates elementary school teachers' perceptions of school-based professional development (SBPD) in Kosovo, with an emphasis on the need for sustainable, context-responsive professional growth.MethodsA quantitative descriptive design was applied. Data were gathered from a representative sample of 150 primary school teachers across three municipalities in Kosovo. Variables analyzed included teaching experience, identified professional development needs, preferred training modalities, and mentoring frameworks.ResultsThe findings indicate a strong demand for updated and differentiated professional development programs, irrespective of teaching experience or training background. Professional development activities were found to enhance instructional practices and pedagogical skills. Perceptions of mentoring differed: experienced teachers valued modeling and peer support, while early-career teachers preferred structured guidance.DiscussionThe results underscore the need for flexible and targeted SBPD strategies. Integrating mentoring into PD programs emerges as a key component for sustainable capacity building and overall educational improvement.